Design and performance quantification of VTOL systems for a canard aircraft. (28th October 2021) - Pedro, S.; Tomás, D.; Lobo do Vale, J.; Suleman, A.
Abstract: The design and performance quantification of four Vertical Take-Off and Landing (VTOL) architectures for a canard-type aircraft configuration are presented. The aero-structural sizing of the canard configuration and the sizing procedure for the proposed VTOL configurations are described and discussed. The proposed VTOL architectures are based on a range of rotor distances to the centre of gravity, quad- and tri-rotor configurations, retractable front rotors and tilt rear rotors. The aerodynamic performance, total installed power and VTOL system mass were modelled and experimentally validated. The results show that a fully exposed VTOL system penalises the Lift-over-Drag (L/D) ratio significantly relative to a clean configuration. The VTOL system mass can be reduced by up to 32% by using a tilt tri-rotor configuration when compared with an equidistant quad-rotor+pusher configuration. The fraction of installed power usable for forward flight can be increased by up to 80% with a tilt configuration. For the proposed mission, the range can be significantly increased if a tri-rotor tilt configuration is adopted in place of an equidistant quad-rotor+pusher configuration.